2019
DOI: 10.1142/s1793292019500139
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Loaded CuS Nanoparticles Conjugated with GFLG: A Novel Drug Delivery System for Lymphoma Treatment

Abstract: Doxorubicin (DOX) plays an important part in lymphoma treatment. However, various side e®ects on normal tissues restrict its clinical use. Nanocarriers connected by Gly-Phe-Leu-Gly (GFLG) can be equipped with the advantages of nanoparticles (NPs), their enhanced permeability and retention (EPR) e®ect, and surface modi¯ability. Nanocarriers can also be speci¯cally enzymatically hydrolyzed by cathepsin (Cath) B, a kind of enzyme highly expressed in tumor cells. In this work, we proposed a novel drug delivery sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Tumor environment-responsiveness of GFLG was also utilized by Jiang and colleagues who used DOX as a drug of interest, which has only 5% bioavailability after oral administration [102]. DOX is the most well-known anthracycline antibiotic that has been successfully used as an anti-cancer drug to treat hematological and solid tumor malignancies for more than 40 years [103].…”
Section: Enzyme-responsive Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor environment-responsiveness of GFLG was also utilized by Jiang and colleagues who used DOX as a drug of interest, which has only 5% bioavailability after oral administration [102]. DOX is the most well-known anthracycline antibiotic that has been successfully used as an anti-cancer drug to treat hematological and solid tumor malignancies for more than 40 years [103].…”
Section: Enzyme-responsive Peptidesmentioning
confidence: 99%
“…Intracellular in vitro accumulation studies showed almost two-fold higher relative fluorescence intensities for CuS-GFLG-DOX in comparison to free DOX. The proposed DDS also generated an enhanced apoptosis rate in Raji cell lines compared to the control [102]. Wang and colleagues also used a GFLG-conjugated DDS to deliver DOX.…”
Section: Enzyme-responsive Peptidesmentioning
confidence: 99%
“…Various techniques, such as nanotubes, 18 nanowires, 19 and NPs, 20 have been used to produce CuS NPs. In fact, CuS NPs have the advantages of relatively high yield, small size, low cytotoxicity, low production cost, and good biocompatibility 21 . CuS NPs make them appropriate for numerous applications in catalysis, 22 molecular imaging, 23 photothermal therapy, 24–26 drug delivery, 27 electrodes, 28 etc.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, CuS NPs have the advantages of relatively high yield, small size, low cytotoxicity, low production cost, and good biocompatibility. 21 CuS NPs make them appropriate for numerous applications in catalysis, 22 molecular imaging, 23 photothermal therapy, [24][25][26] drug delivery, 27 electrodes, 28 etc. In addition to the increased single-therapy threshold by the delivery system, to obtain an optimized anticancer influence, CuS NPs can act as specific radiosensitizers.…”
Section: Introductionmentioning
confidence: 99%